A Multifactorial Approach to Reduce Cardiovascular Disease in Type 2 Diabetes Mellitus: Now More Than Ever. Issue 1 (1st January 2016) - Basile, Jan N.
ABSTRACT: Managing cardiovascular (CV) risk is an important part of caring for patients with type 2 diabetes mellitus, as the disease itself confers CV risk. Many CV risk factors (such as hypertension, dyslipidemia, and obesity) have been found to be more common among individuals with diabetes than in the general population. A growing body of evidence provides guidance for clinicians on how to balance control of hyperglycemia with management of these risk factors. Newer classes of antihyperglycemic agents have been associated with beneficial effects on several CV risk factors; several studies evaluating the effect of these newer diabetic medications on CV outcomes have been published, and several more are in progress. While evidence continues to unfold about the benefits of risk factor control in patients with type 1 diabetes mellitus, this article reviews evidence related to risk-factor control in patients with type 2 diabetes mellitus as well as recent findings on the effect of newer drug classes on CV risk factors and outcomes. Favorably altering CV risk factors appears to improve outcomes, and is more important now than ever before.